Dynamics of Cyanogens and In-Vitro Degradability of Cassava Peels as an Indicator of its Nutritional Value as Animal Feed - Taabu, H.L.; Ndyomugyenyi, E.K.; Mutetikka, D.; Wasswa, D. (Livestock Research for Rural Development, 2015)
The in-vitro degradability of cassava peels and its relationship with the cyanogenic potential of five cassava varieties grown in Uganda was investigated to study the potential of cassava peels as an energy source in animal feeds. The cassava varieties included NASE 3, NASE 4, NASE 10, TME 14 and Tongolo. The first four varieties were considered to be of low to medium cyanogenic potential (CNp), while the last one contained high CNp. Cassava peels had 25.5 ± 6.6% dry matter (DM), 86.6 ± 0.9% organic matter (OM) and 56.8 ± 5.8% neutral detergent fibre (NDF). Degradability of DM, OM and NDF was 74.8± 4.2%, 74% ± 7.5% and 44.2 ± 7.5% respectively. Total cyanogenic potential and free hydrogen cyanide (HCN) in the fresh peels ranged from 923 to 2815 and 33 to 676 mg HCN equivalent kg-1 DM respectively. These levels dropped by 27- 88% and over 90% respectively, when the peels were dried. For all varieties, the residual cyanogenic potential after drying the peels fell within the safety limits recommended by FAO/WHO for food and feed. The study showed that using fresh peels in sufficient amounts for feeding animals, particularly monogastrics, is potentially harmful due to high cyanogenic potential. Drying the peels can, however, reduce the cyanide toxicity risks. The low NDF degradability reduces the nutritional value of cassava peels if they are used as a sole source of energy in ruminant diets.
Keywords: cassava varieties, cyanogenic potential, cyanide toxicity, drying, energy source, livestock